The ‘Scholar Wife’ Examining the ‘Gender Paradox’ - Mishra, Preeti Vivek (JOURNAL OF INDIAN EDUCATION, 2019)
This paper explores perceptions, expressions and negotiations of gender in the complicated context of the ‘scholar wife’. The assertion about ‘complicated context’ positions draws upon scholar wives constituting a ‘unique duality’, wherein their existential positions simultaneously situate them in the realm of traditional masculinities and femininities. The theoretical-epistemological lexicon for this undertaking is borrowed from the postcolonial feminist perspectives because of their denial of metanarratives and the critical scrutiny of the colonisation of gender discourse. The analysis draws upon theoretical postulations as well as primary data obtained through in-depth case studies of two ‘Scholar wife’(ves). The paper seeks to understand whether scholarship has been emancipatory for the ‘scholar wife’(ves), whether they are able to scrutinise the knowledge or power relations and whether they do critically analyse engendering.